Socio‐economic differentiation from a class‐analytic perspective: The case of smallholder tree‐crop farmers in Limpopo, South Africa. (6th August 2019) - Olofsson, Malin
Abstract: South African agrarian policy aims to integrate smallholder tree‐crop farmers into high‐end value chains with growth and employment potential, generally neglecting socio‐economic differentiation amongst them. This paper aims to analyse socio‐economic differentiation amongst tree‐crop farmers in Vhembe District, Limpopo, using a class‐based analysis based on livelihood diversification and accumulation. Cluster analysis of survey data and semi‐structured interviews reveals that most tree‐crop farmers engage in petty commodity production, internally differentiated by their combination of income sources and livelihood strategies. Farmers' ability to engage in accumulation and upward class mobility is generally severely constrained by limited access to capital. Agricultural diversification offers livelihood potential but limited possibility for accumulation, whereas salaried nonfarm work offers more promising prospects for accumulation but limited livelihood opportunities. A minority demonstrated characteristics of small‐scale capitalist farmers, internally differentiated by their reliance on salaried employment or agricultural production. The findings challenge the notion of an undifferentiated class of market‐oriented smallholders.